Reduced occludin expression is related to unfavorable tumor phenotype and poor prognosis in many different tumor types: A tissue microarray study on 16,870 tumors. - Seyma Büyücek; Florian Viehweger; Viktor Reiswich; Natalia Gorbokon; Viktoria Chirico; Christian Bernreuther; Florian Lutz; Simon Kind; Ria Schlichter; Sören Weidemann; Till S Clauditz; Andrea Hinsch; et al. (PLoS ONE)
Occludin is a key component of tight junctions. Reduced occludin expression has been linked to cancer progression in individual tumor types, but a comprehensive and standardized analysis across human tumor types is lacking. To study the prevalence and clinical relevance of occludin expression in cancer, a tissue microarray containing 16,870 samples from 148 different tumor types and 608 samples of 76 different normal tissue types was analyzed by immunohistochemistry. Occludin immunostaining was observed in 10,746 (76.6%) of 14,017 analyzable tumors, including 18.9% with weak, 16.2% with moderate, and 41.6% with strong staining intensity. Occludin positivity was found in 134 of 148 tumor categories and was most frequent in adenocarcinomas (37.5-100%) and neuroendocrine neoplasms (67.9-100%), less common in squamous cell carcinomas (23.8-93%) and in malignant mesotheliomas (up to 48.1%), and rare in Non-Hodgkin's lymphomas (1-2%) and most mesenchymal tumors. Reduced occludin staining was linked to adverse tumor features in several tumor types, including colorectal adenocarcinoma (advanced pT stage, p < 0.0001; L1 status, p = 0.0384; absence of microsatellite instability, p < 0.0001), pancreatic adenocarcinoma (advanced pT stage, p = 0.005), clear cell renal cell carcinoma (high ISUP grade, p < 0.0001; advanced pT stage, p < 0.0001; high UICC stage, p < 0.0001; distant metastasis, p = 0.0422; shortened overall or recurrence-free survival, p ≤ 0.0116), papillary renal cell carcinoma (high pT stage, p < 0.0001; high UICC stage, p = 0.0228; distant metastasis, p = 0.0338; shortened recurrence-free survival, p = 0.006), and serous high-grade ovarian cancer (advanced pT stage, p = 0.0133). Occludin staining was unrelated to parameters of tumor aggressiveness in breast, gastric, endometrial, and thyroidal cancer. Our data demonstrate significant levels of occludin expression in many different tumor entities and identify reduced occludin expression as a potentially useful prognostic feature in several tumor entities.